Body image distortion, perfectionism and eating disorder symptoms in risk group of female ballet dancers and models and in control group of female students - Zoletić, Emina (Array, 2009)
The aim of this research was to examine differences among two groups of girls, models and ballerinas (with risk factors – experimental group) and young students (control group), in body image preception, body mass index, neurotic perfectionism, body – image distortion and simptoms of eating disorders. The research was conducted with 91 participants divided in two groups, control group – 55 students at University of Sarajevo and experimental group – 13 professional ballerinas, 23 professional models. Based on the results in this study, we may conclude that there are groups of people who have risk factors for developing some kind of eating disorder, so it would be desirable to create a preventive intervention for young ballerinas and models, but also for those people who coach them, trainers, instructors and managers. For other population groups with risky behavior such as young children, a prevention plan and modifications of cultural influences on people's opinion of body image are extremly important